Implementation of Discovery Learning Model to Improve Student Learning Outcomes in Aqidah Akhlak Learning at MIS PUI 1 Talaga - Laeli Firdaini; Yudi Hamdan Dardiri (Indonesian Journal of Education and Social Humanities, 2025)
This study aims to describe the improvement of learning achievement through the discovery learning model in learning Akidah Akhlak for Class IV students at MIS PUI 1 TALAGA. The method used in this study is the Classroom Action Research method. This method is carried out in four stages, namely planning, action, observation and reflection. The four stages are in one cycle that is carried out repeatedly with the same steps and remains focused on how to solve problems (answers) by finding it yourself, investigating it yourself and searching for information using the discovery learning model. This study is descriptive qualitative. In collecting data, observation and test methods are used. The observation method is used to measure the activities of teachers and students in each cycle. While the test method is used to determine student learning outcomes after participating in learning using the discovery learning model. The results of this study indicate that the use of the discovery learning model can improve the learning outcomes of Akidah Akhlak for Class IV students at MIS PUI 1 TALAGA, namely 57% in cycle I, 74% in cycle II, and 100% in cycle III. Based on the results of the data analysis obtained, it can be concluded that learning Akidah Akhlak using the discovery learning model for Class IV students at MIS PUI 1 TALAGA.